2004
DOI: 10.4049/jimmunol.173.8.4791
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model for Lymphocytic Infiltration of the Thyroid Gland Generated by Transgenic Expression of the CC Chemokine CCL21

Abstract: Lymphocytic infiltrates and lymphoid follicles with germinal centers are often detected in autoimmune thyroid disease (AITD), but the mechanisms underlying lymphocyte entry and organization in the thyroid remain unknown. We tested the hypothesis that CCL21, a chemokine that regulates homeostatic lymphocyte trafficking, and whose expression has been detected in AITD, is involved in the migration of lymphocytes to the thyroid. We show that transgenic mice expressing CCL21 from the thyroglobulin promoter (TGCCL21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 62 publications
5
64
0
Order By: Relevance
“…Furthermore, expression of CXCL13 was demonstrated in lymphoid aggregates in various chronic inflammatory autoimmune diseases affecting mucosa-associated tissue, the thyroid, and the brain (6)(7)(8)20,21). More direct evidence for a critical role of CXCL13 and CCL21 in the de novo formation of lymphoid tissue has been provided by the finding that ectopic transgenic expression of either chemokine in pancreatic islets or of CCL21 in the thyroid gland is sufficient to trigger lymphoid neogenesis (22)(23)(24).…”
mentioning
confidence: 83%
“…Furthermore, expression of CXCL13 was demonstrated in lymphoid aggregates in various chronic inflammatory autoimmune diseases affecting mucosa-associated tissue, the thyroid, and the brain (6)(7)(8)20,21). More direct evidence for a critical role of CXCL13 and CCL21 in the de novo formation of lymphoid tissue has been provided by the finding that ectopic transgenic expression of either chemokine in pancreatic islets or of CCL21 in the thyroid gland is sufficient to trigger lymphoid neogenesis (22)(23)(24).…”
mentioning
confidence: 83%
“…Transgenic mice expressing IL-12 in the thyroid had moderate primary hypothyroidism due to a direct cytokine effect on thyrocytes (35). Conversely, despite extensive thyroid lymphocytic infiltration, transgenic mice expressing the chemokine CCL21 in the thyroid (36) had normal thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…The role of LT in the context of lymphoid neogenesis, development of autoimmune diseases and inflammatory disorders was further investigated in vivo (Picarella et al, 1992;Kratz et al, 1996;Luther et al, 2000;Drayton et al, 2003Drayton et al, , 2006Gommerman and Browning, 2003;Martin et al, 2004;Heikenwalder et al, 2005Heikenwalder et al, , 2008Haybaeck et al, 2009). These studies revealed that ectopic LT expression suffices to generate lymphoid-like structures (Picarella et al, 1992;Kratz et al, 1996;Gommerman and Browning, 2003;Heikenwalder et al, 2005;Haybaeck et al, 2009), also termed tertiary lymphoid organs or tissues.…”
Section: Lt and Inflammationmentioning
confidence: 99%